Examining subacute nurses' roles in a changing healthcare context. Issue 13 (18th March 2020) - Digby, Robin; Bolster, Danielle; Hughes, Leanne; Perta, Andrew; Bucknall, Tracey K.
Abstract: Aims and objectives: To explore and describe nurses' role in the rehabilitation and care of patients in one subacute care facility in Melbourne, Australia. Background: The role of nurses in subacute care and within the rehabilitation team is evolving and remains unclear. Design: Mixed methods. Methods: Fourteen nurses from seven rehabilitation and geriatric evaluation and management wards in one subacute facility in Melbourne, Australia, were observed in practice for two hours and then interviewed. Activities were recorded electronically. Interviews were audio‐recorded and transcribed. Data were analysed using content analysis. The study complied with the Consolidated Criteria for Reporting Qualitative Research (COREQ). Results: Three main themes are as follows: (a) Nurses as rehabilitators; (b) Teamwork in rehabilitation; and (c) The changing context of subacute care. Nurses prioritised patient personal and clinical care above other responsibilities. They were largely excluded from team decision‐making because clinical responsibilities precluded them from attending team meetings. Unsuitable buildings, increased patient acuity and time constraints were further challenges. Conclusions: Nurses have a multifaceted role in patient rehabilitation that is poorly understood. An evaluation of the nursing role within the interdisciplinary team, skills and processes of care may increase understanding, and improve communication and relationships between disciplines potentially benefiting patients. Role clarity and differentiation in nursing skills are required within the nursing workforce. Relevance to clinical practice: Nurses have a unique role in both clinical care and rehabilitation of patients, and as part of the interdisciplinary team. Respectful professional relationships need fostering within the interdisciplinary team to achieve optimal patient outcomes. The way that team meetings and decision‐making occur in the subacute wards requires adjustment to ensure that the valuable contribution of nurses, both to the interdisciplinary team and to the rehabilitation of patients, is used and acknowledged to improve patient care.